2012
DOI: 10.1194/jlr.m024471
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhances ABCA1 expression and cholesterol efflux through a p38-dependent pathway in macrophages

Abstract: ATP-binding cassette transporter A1 (ABCA1) plays a crucial role in exporting cholesterol from macrophages, a function relevant to its involvement in the prevention of atherosclerosis. Quercetin, one of flavonoids, has been described to reduce atherosclerotic lesion formation. This study is aimed to investigate the effect of quercetin on regulation of ABCA1 expression and to explore its underlying mechanisms in macrophages. The results show that quercetin markedly enhanced cholesterol efflux from macrophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…However, protein expression of SR‐BI was not affected by the presence of QA or quercetin. Previous studies have indicated that flavonoids may activate ABCA1 by up‐regulation of peroxisome proliferator‐activated receptor γ and liver X receptor α 21; another research study showed that quercetin enhances ABCA1 expression through a p38‐dependent pathway in macrophages 48. Our previous data indicated that both quercetin and exogenous N ‐acetylneuraminic acid could improve RCT‐related protein expression in apoE‐deficient mice 49.…”
Section: Discussionmentioning
confidence: 84%
“…However, protein expression of SR‐BI was not affected by the presence of QA or quercetin. Previous studies have indicated that flavonoids may activate ABCA1 by up‐regulation of peroxisome proliferator‐activated receptor γ and liver X receptor α 21; another research study showed that quercetin enhances ABCA1 expression through a p38‐dependent pathway in macrophages 48. Our previous data indicated that both quercetin and exogenous N ‐acetylneuraminic acid could improve RCT‐related protein expression in apoE‐deficient mice 49.…”
Section: Discussionmentioning
confidence: 84%
“…The research from Ponnusamy et al points out that specific inhibition of the ERK pathway could block autophagy in the pathogenesis of renal fibroblasts 51. Furthermore, TAK1 is an important signalling pathway located upstream of p38 and ERK, which play critical roles in various types of physiological processes52, 53 . Kim SI showed that TGF‐β1 induced autophagy in mesangial cells via the TAK1‐MKK3‐p38 signalling pathway 54.…”
Section: Discussionmentioning
confidence: 99%
“…Considering its lipid-lowering effects, quercetin may play an important role in the development of atherosclerosis by regulating RCT. An in vitro study has indicated that quercetin may activate ATP-binding cassette (ABC) A1 by up-regulating peroxisome proliferator-activated receptor γ (PPAR-γ) and liver X receptor α (LXR-α) [8], while other research showed that quercetin enhances ABCA1 expression through a p38-dependent pathway in macrophages [9]. Our previous data indicated that quercetin improves the expression of RCT-related proteins in apolipoprotein E-deficient ( apoE −/− ) mice [3].…”
Section: Introductionmentioning
confidence: 99%